IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT THROUGH CONCEPT SENTENCE MODEL AT THE EIGHTH GRADE OF SMP SWASTA IMANUEL TELUKDALAM - Dewi Damai Duha (Universitas Nias Raya, 2023)
The aim of this research is to improve students’ ability in writing descriptive text through Concept Sentence Model (CSM). The kind of this research was Classroom Action Research (CAR) which was done in two cycles. It was conducted at the Eighth Grade of SMP Swasta Imanuel Telukdalam that consisted of 22 students, the female are 11 students and male were 11 students. The instruments of collecting the data were observation paper and written test. The result showed that, the researcher’s observation paper in cycle I for the first meeting was 56% and second meeting was 67%. In the cycle II for the first meeting was 79% and second meeting 100%. The result of the student’s observation paper in the cycle I for the first meeting was 43% and second meeting was 55%. In the cycle II for the first meeting was 55% and the second meeting was 72%. Furthermore, the result of the test in cycle I, students who passed was 6 students or 27% while the students who failed as 16 students or 73% the average score was 53. Therefore, cycle I was not unsuccessful so the researcher continued in cycle II. In the cycle II, the students who passed the MCC were 20 students or 91% while the students who failed was only 2 students or 9% with the average score was 73. In this second cycle, The students are more active in learning, the students can study in groups and could share their opinions each other, students felt enjoy the class and more creatively. Therefore, Concept Sentence Model was suitable to improve the students’ vocabulary mastery. Therefore, researcher suggested the English teacher to apply Concept Sentence Model in teaching writing, for the students, concept sentence model is usefull and helpful in writing ability. Then for the next researcher, this research can be a source or reference of knowledge about this method in doing research.